Generational cohorts and new venture creation. (1st January 2014) - Kariv, Dafna; Filion, Louis Jacques; Borges, Cândido
This research attempts to decode differences between generational cohorts, especially BBers and Gen-Xers, in the way they use resources to address difficulties at the initiation, preparation, start-up and operations stages of new venture creation. Drawing on generational cohort theory, business stage models and the RBV, we examine differences in the way each cohort addresses difficulties and identifies the most appropriate resources to overcome those difficulties. A sample of 201 Canadian entrepreneurs was surveyed in order to identify significant generational differences in the identification and solution of difficulties at the different stages. More pronounced differences were observed at the more advanced stages, and were mainly associated with financial difficulties. Our study contributes to existing knowledge on generational entrepreneurial performance, and highlights the relevance of exploring how resources are selected and used in order to address different kinds of difficulties.